2013
DOI: 10.3109/09513590.2013.819086
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between plasminogen activator inhibitor-1 (PAI-1) promoter 4G/5G polymorphism and metabolic/proinflammatory factors in polycystic ovary syndrome

Abstract: Polycystic Ovary Syndrome (PCOS) is the most common cause of subfertility associated to metabolic disorders. The aim of this study was to correlate metabolic and proinflammatory factors in women with PCOS. The frequency of Plasminogen Activator Inhibitor-1 (PAI-1) promoter 4 G/5 G polymorphism was also compared to healthy controls. We evaluated 79 PCOS and 79 healthy women. PAI-1 levels are positively correlated with proinflammatory factors in PCOS group. 4 G allele in PAI-1 gene was more frequent in PCOS and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 29 publications
0
11
1
Order By: Relevance
“…Accordingly, obese women with PCOS presented increased levels of PAI-1. Moreover, the 4G allele in PAI-1 gene was more frequent in the PCOS group, and the 4G/4G genotype was associated with the highest PAI-1 levels in this population (Sales et al 2013).…”
Section: Pathophysiology Of Pcosmentioning
confidence: 67%
See 2 more Smart Citations
“…Accordingly, obese women with PCOS presented increased levels of PAI-1. Moreover, the 4G allele in PAI-1 gene was more frequent in the PCOS group, and the 4G/4G genotype was associated with the highest PAI-1 levels in this population (Sales et al 2013).…”
Section: Pathophysiology Of Pcosmentioning
confidence: 67%
“…In a casecontrol study that included 79 patients with PCOS and 79 healthy controls, we have demonstrated that PAI-1 levels are positively correlated with proinflammatory factors in the PCOS group. PAI-1 has a positive correlation with glycemia, BMI, abdominal circumference, HOMA-IR, VLDL-c, LAP, triglycerides, vitamin D and soluble vascular cell adhesion molecule-1 (sVCAM-1) levels (Sales et al 2013). Accordingly, obese women with PCOS presented increased levels of PAI-1.…”
Section: Pathophysiology Of Pcosmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the systemic low-grade inflammation observed in patients with PCOS is also characterized http://dx.doi.org/10.1016/j.cyto.2015.06.008 1043-4666/Ó 2015 Elsevier Ltd. All rights reserved. by elevated interleukin-18 levels, plasminogen activator inhibitor-1 levels, endothelial dysfunction, and oxidative stress [11,15,16]. New evidence suggests that the immune system exacerbates clinical features and can be associated with other important aspects of PCOS, including insulin resistance and cardiovascular disease [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…During the extraction of data, 1 article was excluded owing to overlapping data [25], and 2 articles were excluded as the distribution of genotypes deviated from HWE [26,27]. 10 studies met all inclusion criteria and were included in the meta-analysis [15][16][17][18][19][20][21][22][23][24].…”
Section: Discussionmentioning
confidence: 99%